2003
DOI: 10.1053/jlts.2003.50144
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of hepatocellular carcinoma in liver transplant recipients adds predictive power for determining recurrence-free survival

Abstract: The goal of this study was to determine whether a panel of tumor suppressor gene markers of allelic loss could serve as a representative indicator of gene damage and thereby provide further discriminative power over current staging systems for recurrence-free prognostication in patients undergoing liver transplantation in the presence of hepatocellular carcinoma. The paraffin blocks from 103 cases of hepatocellular carcinoma were obtained, and cellular targets were selected for tissue microdissection genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 36 publications
5
91
0
2
Order By: Relevance
“…For this reason, the standard criteria for LT for HCC are the Milan criteria: patients within the Milan criteria had acceptable or far better 5-year DFS of more than 80% whereas patients beyond the Milan criteria had around 50% 5-year DFS. To expand the criteria for LT for HCC further, more detailed selection criteria representing tumor biology [22, 33, 34] and more aggressive pretransplant neoadjuvant therapy for downstaging [35, 36] would be required as well as a more generous philosophy of acceptance of a 5-year DFS of around 50%.…”
Section: High Cost and Lifelong Immunosuppression For Ltmentioning
confidence: 99%
“…For this reason, the standard criteria for LT for HCC are the Milan criteria: patients within the Milan criteria had acceptable or far better 5-year DFS of more than 80% whereas patients beyond the Milan criteria had around 50% 5-year DFS. To expand the criteria for LT for HCC further, more detailed selection criteria representing tumor biology [22, 33, 34] and more aggressive pretransplant neoadjuvant therapy for downstaging [35, 36] would be required as well as a more generous philosophy of acceptance of a 5-year DFS of around 50%.…”
Section: High Cost and Lifelong Immunosuppression For Ltmentioning
confidence: 99%
“…A vast amount of information regarding genetic markers and genomic aberrations, as well as gene expression, is being accumulated for the study of HCC (9)(10)(11)(12)(13)(14)(15). The major risk factors for HCC development are now well defined, and some of the multiple steps involved in hepatocarcinogenesis have been elucidated in recent years (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is no agreement on the selection criteria that could simultaneously maximize the number of viable HCC candidates for transplantation and reject the smallest number of those who could have benefited (34)(35)(36). Molecular genetic analyses have shown that genomic changes accumulate during the development and progression of HCC (37)(38)(39)(40). Establishment of a molecularbased method for the classification of HCV-HCC pretransplantation will permit the detection of distinct subgroups of HCC patients with different prognoses, allowing greater accuracy in selection of patients for treatment cure with transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in biomedical technology enable us to detect tumor cells at a molecular level (41,42). Molecular/biologic information is beginning to be incorporated into current staging systems to better predict HCC recurrence (37,43,44). An important question is whether molecular staging will be able to augment the accuracy by which the prognosis of individual patients can be assessed.…”
Section: Discussionmentioning
confidence: 99%